COMPARATIVE EFFECTIVENESS OF THE METHODS OF COPROOVOSCOPIC DIAGNOSING SHEEP STRONGYLOIDOSIS - Sorokova, S. S. (Scientific Progress & Innovations, 2019)
At present, sheep breeding, as well as livestock farming in general, acquires a significant social-political importance. For the successful development of this industry, it is necessary to ensure the veterinary well-being of the livestock population in relation to parasitic diseases, in particular strongyloidosis. Flotation methods are used for lifetime diagnosing nematodoses, including strongyloidosis. Scientists’ experience shows, that all flotation diagnostic methods reveal different effectiveness in detecting different types of nema-tode eggs. Therefore, the purpose of the research was to conduct a comparative analysis of the improved method of coproovoscopic diagnostics by the indicators of diagnostic effectiveness as compared with the well-known methods. The work was done in the laboratory of the Department of Parasitology and Veteri-nary-Sanitary Expert Examination at Poltava State Agrarian Academy. The method improvement was car-ried out by making changes to the basic methodology (of Kotelnikov-Khrenov), namely, the composition of the flotation solution and the period of settling down fecal suspension were changed. It has been experimen-tally established that all the studied methods of coproovoscopic diagnostics (Dakhno, 2003; Natiagla et al., 2016; Kotelnikov-Khrenov, 1972 and the improved one) can detect nematode eggs of Strongyloides papillo-sus (Wedl, 1856) species in the feces samples. At the same time, the most diagnostically effective method was the improved method of lifetime coproovoscopic diagnostics, using a complex two-component mixture of in-organic salts with a specific gravity of 1.32−1.34 g/cm3 as a flotation fluid. It was established that in terms of the number of positive samples, the improved method was more effective than those of Dakhno and Kotelni-kov-Khrenov by 5 and 20 %, respectively. High levels of diagnostic effectiveness were also confirmed by quantitative indicators. Thus, in the conditions of production tests in terms of the average number of detected eggs of Strongyloides in the sample, the improved method was more effective than the analogues: of Kotelni-kov-Khrenov − by 42.27 %, Dakhno − by 31.66 %, and the method of Natiagla et al. − by 23.23 %. Analyz-ing the process of the preparations’ microscopy, made in different ways, it was found that the samples, that were made by the improved method were the most convenient (a small amount of foreign residues) for the research.